Consumption, investment and unemployment: SVAR tests of the effects of changes in the consumption-saving pattern - Roberto Bande-Ramudo; Manuel Fernandez-Grela; Dolores Riveiro-Garcia (Cogent Economics & Finance, 2014)
Swarnajayanti Gram Swarozgar Yojana (SGSY) is a government-sponsored microfinance program. The scheme is based on four features: group lending with joint liability, progressive lending, back-ended subsidy, and social capital. We propose a new model of SGSY having these features: group lending with individual liability, progressive lending, back-ended subsidy, and social capital. "Joint liability" clause of the existing model is replaced with individual liability in the new model. The paper shows that problem of adverse selection is removed in both models, i.e. in "SGSY with group lending and joint liability" and "SGSY with group lending and individual liability." The problem of "moral hazard" is more severe in the existing model of SGSY compared with the proposed model of SGSY. Borrowers are also benefitted from participation in the proposed scheme of SGSY than that in the existing model of SGSY.
Keywords: C22; E2; 330; time-series models; consumption; saving; production; employment and investment